33. PATIENT'S EXPERIENCE WHILE MEDICAL EXAMINATION AND TREATMENT HOSPITAL EARS 199 AND RELATED FACTORS (Vietnam Journal of Community Medicine, 2025)
Objective: To understand the experiences of patients and some factors related to patient experiences when receiving medical care at Hospital 199.Methods: A combined method of quantitative and qualitative research study conducted on 404 patients at Hospital 199. For the quantitative research, data was analyzed using SPSS 20.0 software, and for the qualitative research, data sources were interviewed directly by researchers and transcribed, with content encoded by theme.Results and conclusion: The majority of patients had good experiences in various aspects, reaching 70% or higher. Areas for improvement included long wait times for medical appointments, inconveniences in the medical care process, and certain limitations in facilities that also impacted patient experiences. Therefore, Hospital 199 needs to focus on improving the medical care process, upgrading facilities, and emphasizing communication skills training for healthcare staff.
Keywords: patient experience; healthcare quality; 199 Hospital